Composite biomimetic membrane with artificial water channels
By distributing imidazole tetragonal supramolecular aggregates in crosslinked polyamide films, a bionic film with high permeability and high selectivity was developed, which solved the problem of the reduction of selectivity in the improvement of permeability of existing RO films, and achieved the Low-cost and efficient seawater desalination effect.
Patent Information
- Application Number
- CN202080064152.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2019-09-13
- Filing Date
- 2020-09-09
- Publication Date
- 2025-01-03
- Estimated Expiration
- 2040-09-09
AI Technical Summary
The existing seawater desalination technology is costly and has a high energy consumption. The selectivity of traditional RO membranes is reduced when improving permeability, making it difficult to meet the needs of large-scale applications.
Develop a composite bionic film with artificial water channels. By uniformly distributing imidazole tetragonal supramolecular aggregates in crosslinked polyamide films, the permeability and selectivity of the film are improved, and the colloidal suspension impregnation and interfacial polymerization methods are adopted. Prepare to form a membrane with high water permeability and high selectivity.
The water permeability and NaCl selectivity of the membrane are greatly improved at low cost. The water permeability is 3 to 5 times better than that of traditional RO membranes, the NaCl retention rate exceeds 99%, and the stability is maintained during long-term use.
Smart Images

Figure CN114728241B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of bionic membranes with artificial water channels, in particular to their use in the production and management of drinking water.
[0002] The invention relates to a bionic membrane with artificial water channels, a synthesis method thereof, and use thereof in desalination of brackish water and seawater, production of ultrapure water or filtration of pollutants. Background Art
[0003] Water shortages and the problems associated with a lack of drinking water are well known (Eliasson, J. Nature 2015, 517, 6-7). Dealing with the lack of basic resources is becoming increasingly urgent against the backdrop of a simultaneous increase in population and economic activity. Maintaining a balance between supply and demand has a significant impact on climate change due to emissions generated by industry. In order to cope with the growing demand for water supply, several cutting-edge technologies have been explored in recent decades. As far as water is concerned, the most abundant source to date is still the ocean, which accounts for 97.5% of the total water on Earth (Schewe, J. et al. Proc. Natl. Acad. Sci. 2014, 111, 3245-3250). Today, about 100 million cubic meters of desalinated water are produced every day, with an annual growth rate of more than 10%.
[0004] Current technologies are based on thermal (multiple effect desalination-MED and multistage flash-MSF) and membrane (pressure reverse osmosis, RO, electrodialysis-ED, membrane distillation-MD and direct osmosis-FO), with RO dominating the desalination of seawater or brackish water (Imbrogno, J. et al., Annu. Rev. Chem. Biomol. Eng. 2016, 7, 1-36). Energy consumption has decreased, but even with a maximum thermodynamic efficiency of about 60%, the cost of desalination is much higher than the cost of using surface water or groundwater.
[0005] To this day, desalination remains too expensive a method.
[0006] The minimum energy required to operate at 60% recovery is approximately 1.2 kWh / m 3 , and at 80% recovery this value increases to above 1.5 kWh / m 3(Philip, WA et al. Science, 2011, 333, 712-717). In the future, efficiency can be improved by a) changing the conditions of RO technology or b) improving the membrane. Closed-circuit reverse osmosis will soon allow operation at high recoveries under these conditions, but may require higher effective energy. Over the years, RO desalination technology using thin film composite membranes has made great progress, greatly reducing costs. Recently, it has been emphasized that selectivity is as important as permeability, or even more important (Park, HB et al. Science, 2017, 356, eaab0530). Therefore, it is crucial to innovate in the field of membranes. More than half a century has passed since the design of the first polyamide-PA thin film composite TFC membrane (Cadotte, JE, 1981, US Patent 4,277,344AC).
[0007] In recent years, new materials for improving desalination productivity have been developed, giving rise to emerging research areas, such as nanocomposites (thin film composites - TFNs), which include, for example, zeolite nanoparticles and have improved permeabilities (2-3.5 LMH / bar), but still have reduced selectivity and a low NaCl rejection of about 95%-97% (Pendergast MTM et al., Energy Environ. Sci., 2011, 4, 1946-1971).
[0008] In all cases, increased permeability generally resulted in decreased selectivity, without synergistic improvements in these two performance metrics relative to those of conventional RO membranes.
[0009] In the current company, many technologies are inspired by nature, and most of them are related to macroscopic scale. For example, the molecular properties of biological protein channels are very important for future design of artificial systems that allow the regulation of pore function (e.g., pumping, displacement) under the ion gradient across the lipid membrane. The transmission of water through the cell membrane is carried out particularly along aquaporins (AQPs), which are famous for their high permeability permeability and perfect ion retention (Agre, P. "International Applied Chemistry (Angew.Chem.Int.Ed.)" 2004,43,4278-4290). By adding membrane proteins expected to be used for desalination, these characteristics have inspired the incorporation of AQPs into materials for RO membrane design.
[0010] However, large-scale applications of such systems still suffer from high AQP production costs, low stability, and limitations on manufacturing, membrane operating conditions, and desalination (Tang, CY et al., Desalination, 2013, 308, 34-40).
[0011] A first attempt has been made to compare the permeability of ABA polymer membranes incorporating AQPZ. The modified AQP-ABA membrane exhibited a productivity of 167 μm / s / bar, relative to the productivity of conventional RO membranes (1 μm / s / bar) and ABA polymer-supported membranes without AQP (2 μm / s / bar). In fact, an increase in the permeability of the membrane by about 2 orders of magnitude does not lead to a reduction in energy consumption by the same factor (Kumar, M. et al., Proceedings of the National Academy of Sciences of the United States of America, 2007, 104, 20719-20724). In the second step, in order to obtain membranes with high stability and increased performance in AQPs, a different strategy was adopted, namely using a mixed matrix approach with three main components: i) AQP protein, ii) liposomes into which AQPs were incorporated for protection purposes, and iii) a polyamide substrate encapsulating the liposomes (Zhao, Y. et al. Journal of Membrane Science 2012, 423-424, 422-428). The choice of liposomes is justified by the fact that AQPs are transmembrane proteins and their natural environment is the hydrophobic region of the cell membrane. It has been demonstrated that mixed polyamide membranes based on AQPs on a planar substrate have a higher permeability (4 LMH / bar, +33% relative to a reference polyamide membrane) and a reduced selectivity: the NaCl rejection is 97% (Qi, S. et al. Journal of Membrane Science 2016, 508, 94-103).
[0012] However, these results are still not sufficient for large-scale development.
[0013] Therefore, there is a need to develop new composite biomimetic membranes that overcome the shortcomings found in the prior art. In particular, there is a need for membranes that can significantly reduce costs while having better desalination performance than is typically observed. Summary of the invention
[0014] The applicant has been able to develop a novel composite membrane with artificial water channels (AWC). The membrane according to the invention provides improved performance in terms of water transport and salt retention. I-quadruplex (I4) incorporated into the lipid membrane according to the invention is able to transport up to about 1.5 x 10 6 water molecules / second / channel, although lower than AQP (10 8 Water molecules / second / channel), but can intercept all ions. These characteristics make the membranes according to the present invention highly selective by excluding ions and provide them with high selectivity.
[0015] At present, biomimetic membranes of any nature cannot meet the demanding requirements of RO desalination processes. The membranes according to the invention provide water transport at very high permeability while maintaining a high level of ion rejection. Therefore, the membranes are tolerant to the conditions of use.
[0016] Therefore, the present invention firstly relates to novel biomimetic membrane materials that overcome the various disadvantages of the prior art. Moreover, the preparation method of these novel membrane materials is simple and low-cost. Compared with existing RO membranes, they have improved performance, especially in terms of water permeability, retention rate of salts and organic molecules, and mechanical and chemical stability. Therefore, the present invention improves the permeability and selectivity to water at the same time through the superstructure of soft materials, which have an increased preference for water due to artificial water channels. This is particularly reflected in the synergistic increase level of water permeability (4-5LMH / bar) and NaCl selectivity / retention rate (<99.5%) and its long-term stability. The water permeability of the membrane according to the present invention is 3 to 5 times better than that of conventional RO membranes (1.3-1.5LMH / bar), while ensuring a NaCl retention rate level of more than 99%.
[0017] Therefore, the present invention relates to a composite biomimetic membrane, characterized in that it comprises:
[0018] -Ultrafiltration support membrane,
[0019] - at least one compound of formula I:
[0020]
[0021] in
[0022] R represents a linear or branched C4 to C8 alkyl group, preferably selected from butyl, pentyl, hexyl, heptyl or octyl,
[0023] ·X represents S or O, and
[0024] - Cross-linked polyamide membrane.
[0025] Advantageously, in the composite biomimetic membrane according to the invention, said at least one compound of formula I is in the form of supramolecular aggregates of imidazole quartet type, homogeneously distributed in a rigid matrix formed by a crosslinked polyamide membrane.
[0026] Advantageously, the composite biomimetic membrane according to the invention is characterized in that it comprises:
[0027] -Ultrafiltration support membrane,
[0028] - at least one compound of formula I:
[0029]
[0030] in
[0031] R represents a linear or branched C4 to C8 alkyl group, preferably selected from butyl, pentyl, hexyl, heptyl or octyl,
[0032] ·X represents S or O, and
[0033] - Cross-linked polyamide membrane,
[0034] And wherein the at least one compound of formula I is in the form of supramolecular aggregates of imidazole tetrad type, which are uniformly distributed in the rigid matrix formed by the cross-linked polyamide membrane.
[0035] In the present application, "ultrafiltration support membrane" means any type of microporous support compatible with the envisioned pressure and use. It can be, for example, a microporous support of polyethersulfone (PES) or PVDF (polyvinylidene) cast on a support of a non-woven reinforced fabric of microporous polysulfone (PSF) or polypropylene (PP), polyacrylonitrile (PAN 50 or PAN 450). It can be selected from commercial membranes of types such as M-PS20-GPET and M-PS35-GPP. The molecular weight cutoff (MWCO) of the support can be 10 to 250 kD, preferably 10 to 40 kD, or more preferably 20 to 35 kD, wherein the MWCO point value is 20 kD. The thickness of the support can be on the order of 20 to 200 μm, for example, 20 to 70 μm for the porous support of PSF or PES, and 50 to 150 μm for the support of PET or PP.
[0036] Advantageously, the composite biomimetic membrane according to the present invention can be selected from membranes wherein the molecular weight cut-off of the ultrafiltration support membrane is in the range of 10 to 250 kD, preferably 10 to 40 kD or even more preferably 20 to 35 kD, wherein the MWCO point value is 20 kD. The thickness of the ultrafiltration support membrane can be 20 μm to 200 μm, preferably 20 μm to 150 μm.
[0037] Advantageously, the pure water permeability (WP) of the microporous support may be considered to be in the range of 750 to 1600 LMH / bar, with a point value of WP = 750 LMH / bar for asymmetric membranes for manufacturing seawater and brackish water, and 1600 LMH / bar for PA membranes for synthetic brackish water and tap water.
[0038] Advantageously, the film according to the invention comprises at least one compound of formula I:
[0039]
[0040] in,
[0041] R represents a linear or branched C4 to C8 alkyl group, preferably selected from butyl, pentyl, hexyl, heptyl or octyl,
[0042] ·X represents S or O.
[0043] Advantageously, the compounds of formula I may be chosen from compounds in which R is butyl or hexyl.
[0044] Advantageously, the compounds of formula I may be chosen from compounds in which X represents O.
[0045] Advantageously, the composite biomimetic membrane according to the invention may comprise at least one compound of formula II:
[0046]
[0047] Where R 1 It represents butyl or hexyl.
[0048] Advantageously, in the composite biomimetic membrane according to the present invention, the compound of formula I or formula II is in the form of a supramolecular aggregate of the imidazole tetrad or I-quadrud type as described by Le Duc et al., Licsandru et al. or Barboiu et al. (Y. Le Duc et al., Angew. Chem. Int. Ed. 2011, 50(48), 11366-11372; E. Licsandru et al., Journal of the American Chemical Society (J. Am. Chem. Soc.), 2016, 138, 5403-5409; M. Barboiu, Chem. Commun., 2016, 52, 5657-5665 4. I. Kocsis et al., Science Adv. 2018, 4, eaao5603). Preferably, in the composite biomimetic membrane according to the present invention, the compound of formula I or formula II is in the form of a supramolecular imidazole tetrad or I-quadru aggregate. As defined by Le Duc et al., Licsandru et al. or Barboiu et al., an imidazole tetrad or I-quadru is a self-assembly of four molecules of formula I or formula II and two water molecules. The I-quadru defines the primary organization of the artificial water channel, and the assembly of the channel leads to the formation of supramolecular aggregates uniformly embedded in the polyamide membrane during the implementation of the method of the present invention.
[0049] In the context of the present application, "supramolecular aggregates" means crystalline aggregates that can have an average diameter of 20 to 40 nm. Supramolecular aggregates can be composed of self-organized lamellar phases containing artificial water channels of the imidazole tetrad type. The average size of the non-porous aggregates is generally 20 to 40 nm. According to the distribution observed based on the spoke structure, each aggregate can contain 84,000 molecules, or an average of 14 amol in a crystal with a size of 30 x 30 x 30 nm, and according to the three-dimensionality of the crystal, the ideal distribution is 70 x 50 x 24 molecules of formula I or formula II.
[0050] Advantageously, in the membrane according to the invention, the supramolecular aggregates may comprise from 9 to 18 amol of the compound of formula I or formula II.
[0051] Advantageously, the supramolecular aggregates of the imidazole quartet or I-quartet type are uniformly distributed in a rigid matrix formed by a crosslinked polyamide membrane. The surface density of the aggregates of the molecules of formula I or II may be between 30 and 40 aggregates / 100 μm 2 within the range.
[0052] "Cross-linked polyamide membrane" means a surface membrane produced by in-situ polymerization of cross-linked polyamide. The polyamide is formed from a monomer carrying an amine functional group (hereinafter referred to as "amine monomer") and a monomer carrying an acyl chloride functional group (hereinafter referred to as "acyl chloride monomer"). The monomers can be divalent and trivalent. Since the polyamide membrane is cross-linked, at least one of the monomers used is trivalent.
[0053] Advantageously, the amine monomer may have the formula H2N-R a -NH2 or H2N-R a (NH2)-NH2, R a is a C1 to C20 group, a linear or branched, aliphatic or heteroaliphatic, saturated or unsaturated, cyclic or acyclic aryl or heteroaryl, aralkyl or alkaryl group, optionally containing heteroatoms selected from O, N and / or S. For example, the amine monomer can be a diamine or a triamine (divalent or trivalent). Preferably, the amine monomer can be selected from the group consisting of m-phenylenediamine, o-phenylenediamine, p-phenylenediamine, piperazine, ethylenediamine, polyethyleneimine (e.g. Mn=70000, 10000, 1800 or 600) and melamine.
[0054] Advantageously, the acyl chloride monomer may have the formula ClOC-R b -COCl or ClOC-R b (COCl)-COCl, R bis a C1 to C20 group, a linear or branched, aliphatic or heteroaliphatic, saturated or unsaturated, cyclic or acyclic aryl or heteroaryl, aralkyl or alkaryl group, optionally containing heteroatoms selected from O, N and / or S. For example, the acyl chloride monomer may be a diacyl chloride or a triacyl chloride (divalent or trivalent). Preferably, the acyl chloride monomer may be selected from the group consisting of methanesulfonyl trichloride, terephthaloyl chloride, isophthaloyl chloride and cyclohexane 1,3,5-tricarboxyl chloride.
[0055] Advantageously, at least one of the monomers is trivalent in order to obtain a crosslinked polyamide membrane.Preferably, the monomers used are metaphenylenediamine (MPD) and meta-formyl trichloride (trimesoyl chloride, TMC).
[0056] Advantageously, the cross-linked polyamide membrane may be deposited or formed on the microporous surface of the ultrafiltration support membrane.The thickness of the cross-linked polyamide membrane may be 0.05 to 0.4 μm, preferably 0.08 to 0.15 μm.
[0057] Advantageously, composite biomimetic membrane according to the present invention can be a so-called high-density, low-density or very low-density membrane. For example, a high-density membrane can be prepared with a 0.32M MPD solution and a 3.7mM TMC solution. For example, a low-density membrane can be prepared with a 0.19M MPD solution and a 3.7mM TMC solution. For example, a very low-density membrane can be prepared with a 0.13M or 0.17M MPD solution and a 2.5mM TMC solution.
[0058] The present invention also relates to a method for producing the composite biomimetic membrane according to the present invention, comprising:
[0059] - a step of impregnating the ultrafiltration support membrane with a colloidal suspension comprising at least one compound of formula I, preferably in the form of supramolecular aggregates, and
[0060] - A step of forming a cross-linked polyamide membrane by interfacial polymerization on the surface of the impregnated membrane.
[0061] Advantageously, the method for manufacturing the composite biomimetic membrane according to the present invention comprises the following steps:
[0062] a) impregnating the surface of an ultrafiltration support membrane with a colloidal suspension comprising at least one compound of formula I in the form of supramolecular aggregates:
[0063]
[0064] in,
[0065] R represents a C4 to C8 alkyl group, preferably selected from butyl, pentyl, hexyl, heptyl or octyl,
[0066] ·X represents S or O;
[0067] b) forming a cross-linked polyamide membrane by interfacial polymerization on the surface of the impregnated membrane obtained in step a), and producing the composite biomimetic membrane.
[0068] Advantageously, the colloidal suspension in step a) may comprise at least one compound of formula II:
[0069]
[0070] Where R 1 It represents butyl or hexyl.
[0071] Advantageously, the colloidal suspension in step a) comprises an organic solvent and / or water. Preferably, the organic solvent can be selected from methanol, ethanol, propanol, isopropanol and acetonitrile. The solvent can be a mixture of water and an organic solvent, preferably a mixture of water and ethanol or methanol. The volume ratio of solvent / water can be 70 / 30 to 90 / 10 v / v, preferably 85 / 15.
[0072] Advantageously, the concentration of the compound of formula I or II in the colloidal suspension in step a) of the process according to the invention ranges from 4 mM to 0.15 M, preferably from 21.9 mM to 0.12 M.
[0073] Advantageously, the preparation of the colloidal suspension in step a) of the method according to the invention may comprise the following sub-steps:
[0074] i) dissolving the compound of formula I or formula II in an organic solvent;
[0075] ii) adding water (deionized water or Milli-Q) to the solution obtained in i) in a solvent / water volume ratio of 70 / 30 to 90 / 10 v / v, preferably 85 / 15;
[0076] iii) homogenization under ultrasound, preferably for a period of less than 30 minutes, followed by a rest period, preferably lasting from 1 to 3 hours.
[0077] Advantageously, the concentration of the compound of formula I or II in the solution in step i) of preparing the colloidal suspension in step a) of the process according to the invention ranges from 5.23 mM to 0.18 M, preferably from 21.9 mM to 0.12 M, and more preferably from 33 mM to 83.9 mM.
[0078] Advantageously, the impregnation in step a) of the process according to the invention can be carried out by pouring, spraying or electrospraying the liquid solution onto the surface of the support membrane.
[0079] Advantageously, step a) may be followed by a rest period, preferably of 30 seconds to 5 minutes, before step b) of the method according to the invention. This period ensures that the supramolecular aggregates of the colloidal suspension are uniformly dispersed in the pores of the ultrafiltration support membrane surface.
[0080] Advantageously, the interfacial polymerization in step b) of the method according to the invention may comprise the sub-steps of:
[0081] i) impregnating the surface of the impregnated membrane obtained in step a) with a solution containing a diamine or triamine monomer; and
[0082] ii) impregnating the surface of the impregnated membrane obtained in step i) with a solution containing a diacyl chloride or triacyl chloride monomer;
[0083] iii) polymerizing the impregnated membrane obtained in step ii) by immersing it in water at a temperature greater than or equal to 50°C.
[0084] Advantageously, the ultrafiltration support membrane can be fixed on a base. The base can be a base of stainless steel, aluminum, tempered glass or polytetrafluoroethylene. This can limit the polymerization reaction to the available surface of the ultrafiltration support membrane.
[0085] Advantageously, the amine monomer is dissolved in water (deionized water or Milli-Q). The concentration of the amine monomer in the solution in step i) of the interfacial polymerization in step b) of the process according to the invention may be in the range of 5.8 mM to 0.32 M. Depending on the concentration of the monomer, a high density (H-I4RO) may be obtained by using a 0.32 M solution of the amine monomer (e.g. MPD), a low density (L-I4RO) may be obtained by using a 0.19 M solution of the amine monomer (e.g. MPD), or an extremely low density (XL-I4RO) may be obtained by using a 0.13 or 0.17 M solution of the amine monomer (e.g. MPD).
[0086] Advantageously, the impregnation in step i) of the interfacial polymerisation in step b) of the process according to the invention may take less than 240 seconds, preferably less than 120 seconds.
[0087] Advantageously, the impregnation in step i) of the interfacial polymerisation in step b) of the process according to the invention can be carried out by pouring, spraying or electrospraying the aqueous solution on the surface of the ultrafiltration support membrane.
[0088] Advantageously, after the impregnation in step i) of the interfacial polymerization in step b) of the process according to the invention, the ultrafiltration support membrane is dried to remove any excess solution or traces of residual compounds on the membrane surface. Drying can be carried out with an air stream or using an absorbent material.
[0089] Advantageously, the acyl chloride monomer is dissolved in an organic solvent (e.g. hexane, Isopar G, trichlorotrifluoroethylene, toluene). The concentration of the acyl chloride monomer in the solution in step ii) of the interfacial polymerization in step b) of the process according to the invention may be in the range of 1.4 mM to 11.3 M. Depending on the concentration of the monomer, a so-called high density (H-I4RO) or low density (L-I4RO) membrane may be obtained using a 3.7 mM acyl chloride monomer solution (e.g. TMC) and a so-called very low density membrane (XL-I4RO) may be obtained using a 2.5 mM acyl chloride monomer solution (e.g. TMC).
[0090] Advantageously, the impregnation in step ii) of the interfacial polymerisation in step b) of the process according to the invention can be carried out by dipping, spraying or electrospraying on the surface of the ultrafiltration support membrane.
[0091] Advantageously, the impregnation in step ii) of the interfacial polymerisation in step b) of the process according to the invention may take less than 120 seconds, preferably less than 60 seconds.
[0092] Advantageously, the temperature in step iii) of the interfacial polymerization in step b) of the process according to the invention is greater than or equal to 50°C, preferably a temperature ranging from 50°C to 95°C and even more preferably 95°C.
[0093] Advantageously, the duration of immersion in step iii) of interfacial polymerization in step b) of the process according to the invention may be between 60 and 240 seconds, preferably 120 seconds.
[0094] Advantageously, the method according to the invention further comprises a step c) of rinsing the composite biomimetic membrane obtained in step b). The rinsing can be carried out in an aqueous NaOCl solution (for example at 200 ppm) and / or an aqueous Na2S2O5 solution (for example at 1000 ppm), followed by a second immersion in water (deionized or MilliQ), preferably under conditions similar to those of the polymerization step iii) in step b) of the method according to the invention.
[0095] Advantageously, the membrane according to the invention can be stored, for example, at low temperature (about 4° C.) in deionized water or sodium metabisulfite solution (1 g / L), or protected by a protective layer such as glycerol before any use for filtration.
[0096] According to another aspect, the present invention also relates to the use of the composite biomimetic membrane according to the invention for desalination of brackish water or seawater, production of ultrapure water and / or filtration of pollutants.
[0097] In the context of the present invention, "contaminant" or "contaminating agent" means any element which renders the water unfit for drinking, in particular for toxicological reasons, such as urea, residues of pharmaceutical products (paracetamol, etc.), nitrosamines, boric acid, etc.
[0098] Advantageously, the desalination yield is greater than or equal to 99% (expressed as NaCl rejection, R NaCl ), preferably greater than 99.5% or even up to 99.9%. For example, in the case of drinking water (e.g., where ΔP=6 bar and permeability P=4-5 LMH / bar), R NaCl =99-99.5%), in the case of brackish water (e.g., with 3000 ppm NaCl, ΔP = 15-18 bar, permeability P = 4-5.8 LMH / bar), R NaCl =99-99.8%, or for seawater (e.g., with 35000 ppm NaCl, ΔP=65 bar and permeability P=1.8-2.8 LMH / bar), we get R NaCl =99.5-99.9%.
[0099] "NaCl retention rate" refers to the percentage of salt retained by the membrane, and the value is R = 1-cp / cb, where c p = NaCl concentration of the permeate and c b =NaCl concentration of the feed phase.
[0100] "Permeability to NaCl" means the permeability coefficient of solute B, which is calculated using the actual retention rate R r The value of and the flow rate of the permeate with a feed solution containing 35 g / L NaCl at pH 8 were determined.
[0101] "Brackish water" means water having a NaCl concentration of 500-10000 ppm.
[0102] "Permeability" means the coefficient A corresponding to the permeate flow rate of a pure water feed solution, Jw,s0, divided by the applied pressure difference ΔP.
[0103] "Sea water" means water having a NaCl concentration of 30,000-50,000 ppm. BRIEF DESCRIPTION OF THE DRAWINGS
[0104] Figure 1A schematic procedure of the method according to the present invention is shown: Preparation of the composite biomimetic membrane PA-AWC (I4RO) according to the present invention: impregnation of an ultrafiltration support membrane (AWC) of PS20-GPET with an aqueous solution containing supramolecular aggregates, followed by an aqueous solution containing an amine monomer MPD, followed by an organic solution containing an acid chloride monomer TMC, followed by an interfacial polymerization (IP) reaction, thereby producing a polyamide (PA) polymer membrane incorporating water channels within the cross-linked biomimetic layer PA-AWC according to the present invention.
[0105] Figure 2 Scanning electron microscope (SEM) images are shown showing cross sections of a reference membrane without TFC channels and a biomimetic membrane I4RO according to the invention; and the nano-organization of supramolecular aggregates of I4 within a polyamide matrix. A) TFC reference membrane (magnification x 240000), B) biomimetic membrane I4RO according to the invention (magnification x 240000) and C) detail of a polyamide PA membrane showing a uniform distribution of supramolecular aggregates (AWC) of I4 over the entire surface of the PA-AWC polymer (30-40 nm white dots) (magnification x 480000).
[0106] Figure 3 Atomic force microscopy (AFM) images of A) TFC reference film (left) and biomimetic membranes B) H-I4RO_1 and C) L-I4RO_2 are shown.
[0107] Figure 4 EDX surface analysis and basic surface distribution of a) TFC reference film and b) hybrid biomimetic membrane H-I4RO_1-HC6 are shown.
[0108] Figure 5 A laboratory system for measuring water permeability, flow rate, and solute retention is shown.
[0109] Figure 6 The performance of desalination of a) brackish water (18 bar) or b) seawater (65 bar) is shown using
[0110] - membranes according to the invention: a) H-I4RO_1, b) H-I4RO_2, c) H-I4RO_3, d) H-I4RO_4, e) L-I4RO_2, f) L-I4RO_3,
[0111] - Reference films: g) TFC, l) DTAB (in AWC),
[0112] - Commercial membranes: h) BW30, i) XLE, j) T82V, k) SW30, k1) SW30HR, k2) SW30XLE, m) GE_AG, u) BW60
[0113] -Nanocomposite membranes: n) TFN-ZIF8, o) TFN-silicate, p) TFN-CTN (Duan et al. Journal of Membrane Science, 2018, 361, 682-686)
[0114] - Functionalized polyamide membranes: r) REFPA, s) HFAPA (La et al. Journal of Membrane Science 2013, 437 33-39), t) AQP (Wang et al. Journal of Membrane Science 2012, 423-424, 422-428), v1) 3DPAN450TFC_1, v2) 3DPAN450TFC_2, v3) 3DPAN450TFC_3, v4) 3DPAN450TFC_4 (Chuwdhury et al. Science, 2018, 361, 682-686).
[0115] Figure 7 Shown are the structural differences between films obtained from HC8 nanocrystal solutions: a) at room temperature (25°C) and b) at 60°C; and films obtained from colloidal solutions of c) HC4, d) HC6 at room temperature according to the invention. DETAILED DESCRIPTION
[0116] The present invention is further illustrated in a non-limiting manner by the following examples.
[0117] Example 1: Synthesis of the biomimetic membrane I4RO according to the present invention.
[0118] Materials and Methods
[0119] Compound HC6 (compound of formula I, wherein X=O and R=hexyl) was synthesized according to the method described by Le Duc and Licsandru (Y. Le Duc et al., Angewandte Chemie International 2011, 50(48), 11366-11372; E. Licsandru et al., Journal of the American Chemical Society, 2016, 138, 5403-5409). Metaphenylenediamine MPD, trimesoyl chloride TMC and hexane were purchased from ALDRICH. The commercial support membranes used were of the type M-PS20-GPET (Nanostone Water, USA) and M-PS35-GPP (Solecta Membranes, USA).
[0120] 31.6 to 65.1 mM of HC6 compound, depending on the product used, was dissolved in 5 mL of ethanol (see Table 1 below).
[0121] 1 mL of deionized water (alcohol: water volume ratio 85 / 15 v / v) was added and then homogenized with ultrasound for 15 minutes. The solution was then allowed to stand for 1 to 3 hours without stirring before use. The solution contained nano-sized (300-400 nm) aggregates (I4).
[0122] The surface of an ultrafiltration support membrane of type M-PS20-GPET or M-PS35-GPP is then impregnated with a solution containing I4 aggregates. The solution is kept on the support surface for about 1 to 5 minutes at room temperature in order to increase the evaporation of the solvent and ensure that the product is uniformly dispersed in the pores on the support surface.
[0123] The formation of the polyamide membrane PA is then carried out, for example, according to the interfacial polymerization method (Cadotte, JE, 1981, US Pat. No. 4,277,344 AC).The amounts of each precursor used to prepare the TFN-AWC membranes given below are presented in Table 1 shown below.
[0124] The ultrafiltration support membranes M-PS20-GPET and M-PS35-GPP were fixed to a stainless steel base with adhesive tape, so that polymerization occurred only on the available surface.
[0125] Metaphenylenediamine MPD was dissolved in deionized water. Using 0.32M MPD solution resulted in the formation of a high density membrane (H-I4RO), using 0.19M MPD solution resulted in the formation of a low density membrane (L-I4RO), and using 0.13M and 0.17M MPD solutions resulted in the formation of an extremely low density membrane (XL-I4RO). The surface of the ultrafiltration membrane M-PS20-GPET or M-PS35-GPP (Table 1) was impregnated by immersing in the MPD solution for 120 seconds to obtain a uniform and homogeneous dispersion.
[0126] The membrane was dried using an air blower to remove any excess solution or traces of residual compounds on the membrane surface.
[0127] Trimesoyl chloride (TMC) was dissolved in hexane (3.7 mM for high-density membranes (H-I4RO) and low-density membranes (L-I4RO), and 2.5 mM for very low-density membranes (XL-I4RO)) and was uniformly dispersed on the surface of ultrafiltration membranes M-PS20-GPET or M-PS35-GPP (Table 1) by immersing the membranes in the solution for 60 seconds.
[0128] Interfacial polymerization occurred and a polyamide film was formed (reference TFC without AWC or biomimetic membrane I4RO).
[0129] It was observed that a thin film of PA-TFC or I4RO was formed on the surface of the supporting membrane, the thickness of the film being about 0.1 to 0.4 μm.
[0130] The obtained membrane was then immersed in 95°C deionized water for about 120 seconds, then rinsed with a 200 ppm NaOCl aqueous solution for about 120 seconds, then immersed in a 1000 ppm Na2S2O5 aqueous solution for about 30 seconds, and finally immersed in 95°C deionized water for about 120 seconds.
[0131] The membranes were stored in deionized water at 4°C or protected with a glycerol protective layer prior to any use in filtration.
[0132]
[0133] Example 2: Methods for static characterization and characterization during filtration of composite biomimetic membranes
[0134] Transmission electron microscopy analysis revealed a high degree of organization at the nanoscale (see Figure 2 ). In fact, the photographs show the formation of a thin film of reference film TFC in polyamide PA with a thickness of 300-350 nm, while the thickness of the biomimetic film I4RO is greatly reduced to 70-150 nm. For the reference film TFC in polyamide PA, these structures have a peak and valley morphology with a thickness of 30 nm, while for the biomimetic film I4RO, its thickness is greatly reduced to 15-20 nm. It is also remarkable to observe the distribution of artificial water channels AWC in the polymer matrix, where the SEM images highlight the formation of supramolecular clusters at the scale of 30-40 nm, resulting in a nanochannel area that is arranged parallel to each other and very uniform in the polyamide matrix.
[0135] Atomic force microscopy (AFM): A Nanoman with an electronic system Nanoscope 5 (Bruker Instruments) was used to measure the surface roughness of TFC and I4RO membranes. The samples were placed directly on a motorized XY stage using tapping mode. The measuring tip used to digitize the samples was from Nanosensors, PPP NCSTR, with a nominal spring constant of 7 N / m and a typical radius of less than 5 nm. The sampling resolution of all images was at least 512 pts / 512 lines for 5 μm 2 (image size), the scanning frequency is 5.5 Hz, and for smaller sizes, the scanning frequency is 0.65 Hz. These AFM images (see Figure 3 ) shows the formation of a film with comparable roughness to the reference membrane TFC in PA, which is greatly reduced for the I4RO hybrid biomimetic membrane.
[0136] Energy dispersive X-ray spectroscopy (EDX): Energy dispersive X-ray spectroscopy (EDX) of the polyamide active layer was performed using an AZTEC system from Oxford Instruments (UK). The sample was transferred to a 0.5 cm 2 The EDX was performed on a carbon strip of 100 mm and at a working distance of 8.5 mm using an accelerating voltage of 10 kV. At least three spectra were captured at different positions and used to calculate the average atomic percentages of C, N and O in the polyamide active layer. After each scan, the EDX analysis software created a table containing the elemental composition of C, N and O. In fact, these analyses showed (see Figure 4 Tables 2 and 3 below) C% and N% enrichment of I4RO biomimetic membrane compared with PA-TFC reference membrane
[0137] element wt% at% C 67.50 76.38 N 3.70 3.59 O 18.39 15.62 S 10.41 4.41 total 100.00 100.00
[0138] Table 2: EDX surface analysis and elemental surface distribution of TFC reference films.
[0139] element wt% at% C 76.00 82.51 N 3.90 3.63 O 13.92 11.35 S 6.17 2.51 total 100.00 100.00
[0140] Table 3: EDX surface analysis and elemental surface distribution of L-I4RO_4 biomimetic membrane.
[0141] Filtration system: A cross-flow laboratory system was used to measure the pure water permeability coefficient (also known as water permeability), permeate flow rate and solute retention rate of all membranes, as well as countercurrent washing experiments. All membranes included TFC reference membranes and I4RO hybrid biomimetic membranes with different properties, I4RO_1, and commercial reverse osmosis membranes ( Figure 5 The laboratory system consisted of a high-pressure pump (Hydra-cell pump, Wanner Engineering, Inc., Minneapolis, MN), a feed tank, a flat-film receiving unit, temperature control, and a data acquisition system. The receiving unit consisted of a rectangular channel with a length of 7.6 cm, a width of 2.8 cm, and a height of 0.3 cm. Therefore, the active surface area of the membrane sample was 23 cm 2 The crossflow was controlled by a floating disc rotor flowmeter and regulated at the operating pressure via a bypass valve and a backpressure regulator (Swagelok, Solon, OH), while the permeate flow was automatically measured for 60 seconds using a balance with a computer interface. The temperature was controlled by a recirculating chiller (Model MC 1200, Lauda-Koenigshofen, )) control, where the stainless steel coil is immersed in the feed tank.
[0142] Measurement of water permeability (A), flow rate and solute retention rate: Before each experiment, the membrane was immersed in water overnight. After the membrane sample was loaded into the cell, the sample was compacted for 6 hours at an applied pressure of 20 bar (290 psi) or 70 bar (1015 psi) until the membrane equilibrium state was stabilized. The applied pressure was then reduced to a value of 18 bar (261 psi) or 65 bar (943 psi), and the pure water flow rate Jw,0 was calculated by dividing the permeate volume level obtained at equilibrium by the surface area of the membrane.
[0143] The membrane permeability coefficient "A" to pure water was calculated from the value of Jw,0, as shown in Table 4.
[0144]
[0145] Then the solute retention rate test was carried out at a constant cross flow rate of 4.5L / min (cross flow velocity of 0.89m / s) and an applied pressure of 65bar (943psi). The feed stream was composed of a 100mM (3000ppm) (Table 5) for filtration at 18bar or a 600mM (35000ppm) (Table 6) NaCl aqueous solution for filtration at 65bar. The pH (8.0 ± 0.1) was adjusted with sodium bicarbonate. The total volume of the feed solution was 5L at the beginning of the retention rate test. The total duration of each retention rate experiment was about 8 hours. After reaching equilibrium, the flow rate Jw of the permeate was calculated by dividing the volume level of the permeate by the surface area of the membrane. Therefore, the observed solute retention rate values were calculated by the solute concentrations in the feed stream and the permeate stream, as shown in Table 4. The solute concentrations in the feed stream and the permeate stream were determined by the conductivity measured using the calibration line. Three different observed rejection values were obtained, one every 30 minutes, and the three values were averaged. The permeability coefficient for solute "B" was also calculated, as shown in Table 4. For all experiments, the inlet water temperature was kept constant at 27°C ± 1°C.
[0146] Mechanical resistance to countercurrent washing: First, using pure water as the feed solution, the membrane samples were compacted under an applied pressure of 70 bar (1015 psi) for 12 hours. This step was followed by permeability, flow rate and rejection tests under the same operating conditions and the same concentrations as described in the previous section. Therefore, the values of A, B and observed rejection were calculated for each membrane. A countercurrent washing cycle was then performed by inducing a reverse flow of the permeate solution from the support to the feed side of the membrane. After decompressing the feed solution, the permeate flow pressure was increased to a value of 116 psi (6 bar), thereby causing the permeate to flow in reverse for 20 minutes. The feed solution was allowed to flow at a lateral flow rate of 4.5 L / min during the countercurrent washing. After 20 minutes, the permeate solution was decompressed and the feed solution was re-pressurized: Permeability, flow rate and rejection tests were performed under the same operating conditions and the same concentrations as described previously, and then the values of A, B and observed rejection were determined. Three cycles of countercurrent washing were performed.
[0147] Chemical stability: To test the chemical stability of the membranes, they were stored for 30 minutes in different solutions containing: (i) sodium dodecyl sulfate 34 mM (pH 11.5) or (ii) ethanol. After this step, the membranes were carefully rinsed with deionized water and tested as described above.
[0148] The results obtained for the saline solutions are shown in Tables 5 to 8 and Figure 6 The filtration results for organic contaminants such as acetaminophen or urea are also shown.
[0149]
[0150]
[0151]
[0152]
[0153] Example 3: Comparison of the efficiency of a biomimetic membrane comprising I-quadruplexes (according to the invention) and a membrane comprising nanocrystals.
[0154] The efficiency of the biomimetic membranes prepared according to the invention was compared with those prepared according to a conventional method which does not use a colloidal suspension but a nanocrystallization method: 50 μL of a 100 or 200 mM HC8 concentrated methanol solution was added to 10 ml of an aqueous MPD solution to obtain a suspension of HC8 nanocrystals (concentration: 0.49 mM or 0.99 mM) with a total volume of 10.05 mL; (MeOH:H2O=0.5:99.5) according to the procedure described in Its van Kocsis, Supramolecular artificial water channels: from molecular design to membrane materials, thesis awarded the degree of PhD in Chemistry and Physical Chemistry of Materials from the University of Montpellier, May 6, 2018 ( http: / / hal.umontpellier.fr / tel-01684404 / document ).
[0155] Table 9 below shows a comparison of the performance (WP = water permeability and salt rejection, %) of AWC-HC4 and AWC-HC6 membranes according to the present invention and a reference thin film composite membrane with AWC-HC8-25 and AWC-HC8-60 membranes repaired according to the method of the ItsvanKocsis document and a reference thin film composite membrane (TFC for "thin film composite membranes").
[0156]
[0157] For the membranes obtained by the nanocrystallization method (not included in the present invention), a slight increase in permeability and a decrease in selectivity were observed compared to the TFC reference membrane. These results are related to the generation of micro defects in the polyamide membrane structure at the interface with the nanocrystals.
[0158] In contrast, membranes AWC-HC4 and AWC-HC6 according to the present invention showed a clear improvement in permeability and significant selectivity.
[0159] Figure 7 The structural differences between the films obtained from the nanocrystalline solution and the films obtained from the colloidal solution are shown. Thus, it can be seen that the film according to the invention is homogeneous, with very homogeneous ridges and valleys arranged over the entire surface of the film. The AWC particles are smaller and interact continuously on the surface of the PA protrusions.
[0160] The composite biomimetic membrane according to the present invention thus provides the following advantages:
[0161] - They are easily prepared by inexpensive synthetic methods. They can be easily produced in large quantities without any expensive equipment and do not require special safety conditions. Moreover, the synthetic strategy through supramolecular self-assembly and interfacial polymerization leads to the production of highly organized membranes containing 30 to 40 nm active areas enclosing artificial water channels in the polyamide PA structure;
[0162] - They have excellent permeability, 4 to 5 times higher (in LPRO brackish water filtration mode) or 2.8 times (in SWRO-seawater filtration mode) than TFC reference membranes, while maintaining selectivity > 99.5% - NaCl rejection. They have been tested under the same filtration operating conditions usually used in conventional processes for desalination. Therefore, this makes them the material of choice for use as RO membranes in desalination modules;
[0163] - They also have remarkable homogeneous properties due to the controlled nanostructure during synthesis. These films also show good stability in alkaline hydrolysis environments and / or solubility in the presence of organic solvents (such as ethanol or methanol) or surfactants (such as dodecyl sulfate).
[0164] The membrane according to the invention has a biomimetic structure in the form of nano-supramolecular aggregates of AWC channels with a soft material structure within a rigid polymer matrix of PA. This special structure of the membrane according to the invention favors water permeability without allowing the transport of cations and anions. This provides advantages in terms of water permeability, thereby increasing their transport capacity while maintaining high ion retention.
[0165] Interesting selectivities for the retention of organic pollutants can also be reported:
[0166] - 2 g / L urea solution (pH = 7) was filtered using a H-I4RO_3 membrane with a permeability of 4.29 LMH / bar and a urea rejection of 70%;
[0167] -100 ppm, 200 ppm, 300 ppm acetaminophen solutions were filtered using H-I4RO_3 membrane with a permeability of 3.76 LMH / bar and the retention rates of acetaminophen were 99.51%, 99.14% and 98.98%, respectively.
Claims
1. A method for manufacturing a composite biomimetic membrane, comprising the following steps: a) impregnating the surface of an ultrafiltration support membrane with a colloidal suspension comprising at least one compound of formula I in the form of supramolecular aggregates: in, -R represents a C4 to C8 alkyl group, -X means S or O; b) forming a cross-linked polyamide membrane by interfacial polymerization on the surface of the impregnated membrane obtained in step a), The interfacial polymerization comprises the following sub-steps: i) impregnating the surface of the impregnated membrane obtained in step a) with a solution comprising a diamine or triamine monomer; ii) impregnating the surface of the impregnated membrane obtained in step i) with a solution containing a diacyl chloride or triacyl chloride monomer; and iii) polymerizing the impregnated membrane obtained in step ii) by immersing it in water at a temperature greater than or equal to 50° C., And the composite bionic membrane is produced.
2. The method according to claim 1, wherein R is selected from butyl, pentyl, hexyl, heptyl or octyl.
3. The method according to claim 1 or 2, wherein the colloidal suspension comprises an organic solvent and / or water.
4. The method according to claim 1 or 2, further comprising the step of flushing the composite biomimetic membrane.
5. A composite biomimetic membrane prepared by the method according to any one of the preceding claims, characterized in that The membrane comprises: -Ultrafiltration support membrane, - at least one compound of formula I: in, -R represents a linear or branched C4 to C8 alkyl group, -X means S or O, and - cross-linked polyamide membrane, and wherein the at least one compound of formula I is in the form of supramolecular aggregates of imidazole tetrads, which are uniformly distributed in the rigid matrix formed by the cross-linked polyamide membrane, and the surface density of the supramolecular aggregates is between 30 and 40 aggregates / 100 μm 2 In the range of , the supramolecular aggregate is a crystalline aggregate with an average diameter of 20-40 nm, and the supramolecular aggregate is composed of a self-organized lamellar phase of artificial water channels containing imidazole tetrads, And wherein very homogeneous ridges and valleys are arranged over the entire surface of the film.
6. The membrane of claim 5, wherein R is selected from butyl, pentyl, hexyl, heptyl or octyl.
7. The membrane according to claim 5 or 6, wherein the molecular weight cut-off of the ultrafiltration support membrane is in the range of 10 to 250 kD.
8. The film according to claim 5 or 6, wherein the compound of formula I is selected from the compounds of formula II: Where R 1 It represents butyl or hexyl.
9. The membrane according to claim 5 or 6, wherein the polyamide membrane has a thickness of 0.05 to 0.4 μm.
10. The membrane according to claim 9, wherein the polyamide membrane has a thickness of 0.08 to 0.15 μm.
11. The membrane of claim 5 or 6, wherein the polyamide membrane is a crosslinked polyamide of diamine or triamine monomers and diacyl chloride or triacyl chloride monomers, at least one of the monomers being trivalent.
12. Use of the composite biomimetic membrane according to any one of claims 5 to 11 for desalination of drinking water, brackish water or seawater.